Recuperation of Non-commercial Trees in Logged Forest in Southern Papua, Indonesia - Agustinus Murdjoko (Jurnal Manajemen Hutan Tropika, 2013)
Someparts of forest in southern Papua Indonesia is used as production forest.  Therefore, cutting is one of factors which has impact to population of trees.  Research was done to see recuperation of non-commercial species (Actinodaphne nitida, Blumeodendron sp.) in logged area.  Integral Projection Models (IPMs) were applied to analyze population dynamics of the 2 species.  Mortality, growth, fecundity, autocorrelation of growth were included in IPMs.  Data were collected from 3 permanent sample plots (3 ha) between 2005-2009 in PT. Tunas Sawaerma, Assiki, and Boven Digul.  Data showed a significance in autocorrelation of growth.  In this research, IPMs can be used to describe recuperation  of the tree species.  Population dynamics occur in which trees have the same survival probability among diameter size, while growth of trees and autocorrelations contribute to the change of population structure of trees.  Elastisity test of growth autocorrelation pointed out that A. nitida and Blumeodendron sp remain to grow faster over time and have a larger contribution to population growth than other species.  In addition, the more faster-growing individuals will have the more significant contributions for population growth rate of A. nitida and Blumeodendron sp.